Comparação entre métodos de extração de DNA em tecido ósseo: método orgânico com digestão pela proteinase K e método com movimento de precessão: utilizando como parâmetros a eficiência de amplificação de STRs autossômicos - Marini, Maria Christina (2014)
The bone is the most challenging tissue for DNA extraction and purification. Expensive commercial kits and specific equipment are often used in forensic laboratories towards that goal. This paper focuses primarily on comparing two methods of DNA extraction from cell degraded bone tissue. In this context is described the classic method and already filed by the forensic laboratories, which uses proteinase K and will be proposed a method not yet routinely used in Forensic Laboratories of Molecular Genetics, which is based on a device that produces a movement of precession. After an exhaustive survey in the archives of the Molecular Genetics Laboratory of Forensic Paraná State Forensic Science, between the years 1998 and 2013, were found 817 cases of human identification, of which 527 with conclusive results, of which 463 were inclusions and 64 exclusions. Of the remaining cases, 85 were processed several times without conclusive results, for technical impossibilities until the present day. The remaining 205 cases were cataloged in the archives of the Laboratory as no appointment, not leave report, canceled, and various tissues. The remaining 85 cases with inconclusive results, were used in this study 45 samples already extracted. The other 40 cases contained very little sample, or were used until the end of the samples sent.